Bullying in the Workplace: The Plight of South African Employees - Calitz, Karin (Potchefstroom Electronic Law Journal, 2022)
This article discusses the prevalence of bullying in South African workplaces as well as the causes and symptoms thereof and the shortcomings in the current protection available to victims. Jurisprudence indicates that in the past victims typically had to rely on the prohibition against harassment in the Employment Equity Act 55 of 1998 (EEA). However, they were often unsuccessful as they could not prove that the bullying took place on a prohibited ground. An analysis of the common law and various other statutes confirms that South African law provides inadequate protection to victims of bullying. A brief overview of measures against bullying in some foreign jurisdictions indicates that bullying is mostly seen as a health and safety concern and that victims do not have to prove that bullying took place on a prohibited ground. This article also discusses the newly adopted Code of Good Practice on the Prevention and Elimination of Harassment in the Workplace (2022 Code) which endeavours to give effect to the International Labour Organisation’s (ILO) Violence and Harassment Convention No 190. The discussion aims to establish whether the 2022 Code will resolve the lacuna in the protection against workplace bullying. The article concludes that this is not the case and recommends that the EEA be amended to define harassment sufficiently wide to include bullying; that the Labour Relations Act 66 of 1995 be amended to provide that an omission by an employer to address harassment (including bullying) could constitute an unfair labour practice; that a national code issued in terms of the Occupational Health and Safety Act 85 of 1993 be adopted to address bullying; and that health and safety legislation be amended to explicitly address bullying in the workplace and provide remedies to victims.